Comparison of NOSES and Conventional Laparoscopic Surgery in Colorectal Cancer: Bacteriological and Oncological Concerns - Ouyang, Qianhui; Peng, Jian; Xu, Shuai; Chen, Jie; Wang, Wen (Frontiers in Oncology, 2020)
Background: Colorectal natural orifice specimen extraction surgery (NOSES) is a new technique for reducing abdominal wall incisions compared to conventional laparoscopy (CL), but it still has oncological and bacteriological concerns. Objective: The purpose of this study is to analyze the peritoneal lavage fluid oncological and bacteriological results in NOSES and CL procedures. Methods: This is a retrospective study of prospectively collected outcomes data. Patients operated with colorectal cancer from January 2016 to December 2019 in Xiangya Hospital were assigned to the group NOSES and the group CL according to the size of the tumor. Prior to dissection, peritoneal lavage fluid was collected for cytological assessment. At the end of the procedure, peritoneal lavage fluid was collected for aerobic culture and cytological assessment. Baseline characteristics and short-term and long-term outcomes for NOSES and CL were compared. Results: Between January 2016 and December 2019, 212 patients were enrolled from our center and 185 patients were analysed (96 and 89 in NOSES and CL groups respectively). The bacterial positive rate of peritoneal lavage fluid was 34.4% vs. 32.6% in NOSES and CL groups, respectively (P=0.80). The positive rate of tumor cells in peritoneal lavage fluid was 7.3% vs. 9.0% in NOSES and CL groups, respectively (P=0.67). Univariate analysis showed that the positive rate of tumor cells in peritoneal lavage fluid was significantly associated with tumor invasion depth and lymph node metastasis (P <0.05). T4 (OR=20.47, 95%CI 1.241-337.661; P=0.04), N1(OR=5.445, 95%CI 1.412-20.991; P=0.01) and N2 (OR=6.315, 95%CI 1.458-27.348; P=0.01) served as independent predictors of peritoneal lavage fluid positive oncology patients. Local recurrence-free survival was not significantly different between two groups (HR=0.796, 95%CI 0.239-2.625; P =0.71). Conclusions: Compared with conventional laparoscopic procedure, NOSES is in conformity with the principle of asepsis and tumor-free technique and can be worthy of clinical application and promotion.